Serum IgG antibodies against Helicobacter pylori low molecular weight antigens 50kDa, 30kDa and Urease A 26 kDa, along with vacuolating cytotoxin A are associated with the outcome of the infection - Manojlović, Nebojša; Tufegdžić, Ivana; Ristanović, Elizabeta; Bokonjić, Dubravko (Vojnosanitetski pregled, 2021)
Background/Aim. We designed and conducted this study due to the fact that results of the previous studies about seroreactivity to low-molecular-weight Helicobacter pylori antigens, cytotoxin-associated gene A (CagA), vacuolating cytotoxin A (VacA) in patients with gastric cancer and peptic ulcer were conflicting. Methods. The Western blot test was performed in 123 patients, 31 with gastric cancer, 31 with duodenal ulcer, 31 with gastric ulcer, 30 with gastritis and functional dyspepsia in order to determine IgG antibodies to H. pylori antigens (CagA, VacA, Heat shock protein 60kDa, Urease B 66 kDa, Flagellin 55kDa, 50kDa, 30 kDa, Urease A 26 kDa, 24 kDa). In this study we analyzed: seroreactivity to H. pylori antigens between group with functional dyspepsia and others; between grades of different histopathological parameters of inflammation of antral and corporal mucosa and between antrum-predominant gastritis and corpus-predominant gastritis + pangastritis groups. Results. It was shown that seropositivity to 50 kDa antigen could be used as a biomarker for functional dyspepsia, seropositivity to 30 kDa antigen for antrum-predominant gastritis and H. pylori colonization in the antrum, to UreaseA26 kDa antigen for pangastritis and corpus-predominant gastritis and degree of inflammation in the corpus. Seropositivity to VacA was the biomarker for gastric cancer and peptic ulcer taken together and inflammation of antral mucosa. Seropositivity to CagA was associated with more intensive inflammation of antral and corporal mucosa, Urease B66 kDa with inflammation of corpus mucosa, but neither of them with specific outcome of H. pylori infection and topographic distribution of gastric inflammation. Conclusion. Serum IgG antibodies to H. pylori antigens 50kDa, and VacA may represent useful biomarkers for the specific outcome of H. pylori infection, while serum antibodies to 30 kDa and UreaseA26 kDa antigens might be used as specific biomarkers for different topographic distribution of inflammation in gastric mucosa.